Handbook of Transportation Policy and Administration - JACK RABIN, T. Aaron Wachhaus, Jr. (Taylor & Francis Group, 2007)
The past three decades have brought sweeping changes to the i eld of transportation. In the United States and other developed nations, deregulation and greater reliance on markets and the private sector has helped to reconi gure the transport industries. The rise of intermodal goods movements and global commerce has produced efi ciencies of operation and a greater interdependence among transport modes. The fundamental importance of transportation in the modern society has been examined by rigorous analysis from a variety of disciplines: engineering, economics, geography, political science, information science, and sociology. Tradeoffs between competing values such as mobility, safety, efi ciency, equity, conservation, aesthetics, and historic preservation have helped to heighten our understanding of the critical position transportationâ€”and policies and management guiding transportationâ€”plays in contemporary life. In the post-September 11 era, transportation security issues have moved to center stage as we grapple with the challenge of protecting our vast transportation system while maintaining its operational efi ciencies and effectiveness. The Handbook of Transportation Policy and Administration represents an effort to bring together under one cover the work of a number of leading experts in the emerging and interdisciplinary i eld we call â€œtransportation studies.â€ It is by no means completeâ€”that would require a multi-volume treatment. However, it is intended to provide professionals in the i eld of transportation, students, scholars, public ofi cials, and informed citizens knowledge of the basic organization of the transportation i eld, the policies guiding its operations and development, case examples of transportation planning, operations and management, connections between the transportation system and other policy arenas, and a picture of how transportation modes and systems are changing under the pressure to remain safe and secure under new types of threats. The volume has been developed under what might be called an â€œopen-endedâ€ approach. The various authors were not expected to test any particular thesis or vision of transportation, but rather to contribute their best thinking on major aspects of transportation policy and administration. The Handbook takes no stand on the contentious issues that often arise in discussions of transportation: which mode of transport should be preferred, should the public or private sector take the lead in making fundamental decisions or running transportation operations, or what discipline holds the key to understanding transportation issues. The reader is provided a broad range of insights, beginning with overviews of many of the major transportation modes and moving through discussions of transportation policy and transportation management to the i nal section on transportation security. Authors include practitioners, current and former, as well as scholars and policy analysts. The focus is primarily on the United States and almost entirely on transportation in the developed world: a weakness, no doubt, and one that we hope will be corrected in a future examination of transportation in other settings.